Test Automation Engineering Handbook Learn and Implement Techniques for Building Robust Test Automation Frameworks - Sambamurthy, Manikandan (Packt Publishing, Limited, 2023)
Understand test automation and implement it in Web, Mobile, and APIs effectively Key Features Learn how to automate your tests with the help of practical examples Understand how to bridge the gap between testing and test automation Explore test automation strategies for different platforms Book Description This book helps you build a better understanding of test automation and aids in bridging the gap between testing and test automation. The book has been divided into three sections with the first section focusing on preparing you for testing and test automation fundamentals. By the end of this section, you'll have an understanding of some common automation terms, definitions, and roles. The second section covers the practical implementation of test automation for mobile, web, API and performance. The third section will help you understand how test automation works with CI/CD, and explore the common issues and pitfalls when executing test automation. By the end of this book, you'll have a better understanding of automation, addressing the common pain points and best practices around test automation. What you will learn Gain a solid understanding of test automation Understand how automation fits into a test strategy Explore essential design patterns for test automation Design and implement highly reliable automated tests Understand issues and pitfalls when executing test automation Discover the commonly used test automation tools/frameworks Who this book is for This book is for manual testers who want to enter the field of test automation and developers who want to learn more about test automation.